Iron-Catalyzed Oxidative Arylmethylation of Activated Alkenes Using a Peroxide as the Methyl Source - Fan, Jian-Hong; Zhou, Ming-Bo; Liu, Yu; Wei, Wen-Ting; Ouyang, Xuan-Hui; Song, Ren-Jie; Li, Jin-Heng (Synlett, 2014)
A novel, simple route for the synthesis of oxindoles is presented via iron-catalyzed oxidative arylmethylation of activated alkenes with peroxides. This work is realized by the use of a peroxide as the methyl source and 1,4-diazabicyclo[2.2.2]octane as the ligand and represents a new access to oxindoles through an alkene oxidative difunctionalization process.
Keywords: iron; alkenes; peroxides; difunctionalization; methylation; oxindoles